Pharmaceutical marketing in the Philippine setting - Lao, Felix M. (Pasig City : Anvil Publishing Inc., 2006)
Pharmaceutical marketing, 4th edition, is the final answer. It aims to help cushion the impact of rising costs of drugs and medicines so pharmaceutical business firms can stay competitive in a highly volatile business environment.
Chapter 1 : The Pharmaceutical health care industry -- Chapter 2 : The Health care business in the Philippines -- Chapter 3 : Pharmaceutical marketing : the marketing systems, markets, and products -- Chapter 4 : The Marketing management process in the drug industry -- Chapter 5 : Product mix : decisions and strategies -- Chapter 6 : Price mix : decisions and strategies -- Chapter 7 : Promotions mix : decisions and strategies -- Chapter 8 : Place mix : decisions and strategies -- Chapter 9 : Formulating and implementing the marketing plan and budget -- Chapter 10 : Community pharmacy : developing competitive advantages -- Chapter 11 : Pharmaceutical marketing during turbulent times : coping the current financial crisis -- Chapter 12 : Health care relationship marketing and core competencies -- Chapter 13 : Advertising pharmaceutical mass marketing.
Includes index.
Keywords: DRUG -- MARKETING; PHARMACEUTICAL -- ECONOMICS -- PHILIPPINES